Engklek as Media Edugames to Improve Knowledge and Attitudes About Waste Classification and Management of Students - Elvi Sandra Widarto; Heru Subaris Kasjono; Sri Haryanti (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Low knowledge and attitudes related to awareness of waste classification and management in children aged 10-12 years. One of the efforts to increase knowledge and attitudes in waste classification and management is the engklek media. This study aims to determine how using engklek as educational media increases knowledge and attitudes about waste classification and management. This study uses a research design, a non-equivalent control Group. The population studied was all SD Keputran 1 Yogyakarta students, as many as 59 students in collecting data using Non-Random Sampling. The data analysis used was quantitative data analysis using the Microsoft Excel 2016 program and the IBM SPSS Statistik 23 program. From this univariate analysis, an average knowledge score was obtained. The pre-test was 4.42, and the post-test was 8.07. While the average attitude score pre-test obtained 36.96, the post-test obtained 47.54 with a p-value of 0.000. Based on the study's results, it can be concluded that the crank game is more effective for increasing knowledge and attitudes about waste classification and management.